Corporate Restructuring: Governance and Control Limits of the Internal Capital Market - Hoskisson, Robert E.; Turk, Thomas A. (Academy of Management Review, 1990)
Corporate restructuring that is sparked by the threat of a takeover provides evidence that corporate governance limits of large diversified (M-form) firms may exist. This paper proposes that poor corporate monitoring, which is due to atomistic ownership patterns and inadequate board of director governance, an emphasis on incentive compensation, and free cash flows, may lead to higher levels of diversification. If diversification results in loss of strategic control and poor performance, the threat of a takeover is likely to be related to the incidence of corporate restructuring. Corporate restructuring, in turn, is likely to (a) result in the correction of inadequate governance patterns, (b) create a more focused diversification strategy, (c) increase strategic control, (d) reduce reliance on bureaucratic control through reduced corporate staff, and (e) increase the performance of the firm and shareholder wealth.